Risk Management in Decision-Making: A Bibliometric Study - Zan Zabila; Ghina Zahira Syahda; Andi Ahmad Aji Ripaldi; Dicko Syahputra; Muhammad Gibran Rustu; Margareth Henrika; Muhammad Ramadhani Kesuma (Indo Publishing, 2026)
This study examines the intellectual landscape of risk management in decision-making through a systematic bibliometric analysis of scholarly publications indexed in Scopus. The study employs a bibliometric method using 168 articles retrieved from Scopus via Boolean keyword search. VOSviewer software was used to conduct co-authorship, co-occurrence, and country collaboration analyses. Publication output has grown significantly over time, reflecting heightened academic interest. Risk management and risk assessment constitute the dominant thematic core, while emerging research clusters reveal a shift toward technology-integrated approaches, including machine learning and big data analytics, alongside growing attention to sustainability and ESG dimensions. Practitioners and policymakers can leverage the identified research clusters to prioritize technology-enabled risk frameworks, particularly in financial decision-making contexts within emerging markets. This study provides a comprehensive mapping of the risk management and decision-making nexus, identifying thematic gaps and underexplored intersections with digital transformation and sustainability that set a future research agenda for financial management scholars.